Power Quality Improvement Using Dynamic Voltage Restorer for Various Line Faults (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Electrical systems are subjected to a wide range of power quality problems which interrupt production processes. Equipment sensitivity may lead to downtime scrap and capacity losses. Also, good power quality saves more energy and money. One approach to address voltage sag problem is by implementing Dynamic Voltage Restorer (DVR) as it gives compensation to sag, swell, improves the line regulation and restores load voltage within a few milliseconds. DVR are a relatively new static VAR device that has seen applications in a variety of distribution and transmission applications. Due to its miniaturization, and cost reliability it includes fast dynamic response. This proposal presents modelling, analysis of voltage sags and correction of power factor for improved power quality using MATLAB/SIMULINK which includes as PI Controller and Discrete PWM generator for the control purpose of DVR